Vector Mechanics For Engineers: Statics and Dynamics - Beer ( Ferdinand P); Johnston (E Russell); Eisenberg (Elliot R) & Others (2007)
Vector Mechanics for Engineers
22.5
Keywords: Vector Mechanics for Engineers